Immigration, Human Capital Formation and Endogenous Economic Growth - Isaac Ehrlich; Jinyoung Kim (Institute for the Study of Labor (IZA), 2015)
Census data from international sources covering 77% of the world's migrant population indicate that the skill composition of migrants in major destination countries, including the US, has been rising over the last four decades. Moreover, the population share of skilled migrants has been approaching or exceeding that of skilled natives. We offer theoretical propositions and empirical tests consistent with these trends via a general-equilibrium model of endogenous growth where human capital, population, income growth and distribution, and migration trends are endogenous. We derive new insights about the impact of migration on long-term income growth and distribution, and the net benefits to natives in both destination and source countries.
Keywords: F22; F43; O15; O4; 330; immigration; human capital formation; endogenous economic growth; migrants; natives; population; long-term income